EXTRACTION OF LACTATE DEHYDROGENASE (LDH) FROM CORN SEEDS AND ROOTS FOR CONVERSION OF PYRUVIC ACID TO LACTIC ACID - Satria, Arfanza
Lactic acid is a compound that is widely used in various types of applications from the health industry, food industry, and chemical industry. Lactic acid is also widely used as an ingredient to make advanced products. One example is that lactic acid can be polymerized into polylactide (PLA) which is a biodegradable plastic for packaging. Most of the lactic acid used in industry is produced through conventional conversion pathways using chemical catalysts with relatively high operating costs, unsustainable, and not environmentally friendly. Therefore, alternative solutions are needed to produce lactic acid. This study aims to identify lactic acid products from the conversion of pyruvic acid by utilizing the enzyme Lactate Dehydrogenase (LDH) from corn plants. This research is expected to be a solution to the problem of the majority of lactic acid production in the industry today. The research was carried out by extracting the enzyme Lactate Dehydrogenase (LDH) with the extraction temperature variations of 5°C, 27°C, and 37°C which were analyzed by the Bradford test. In addition, the activity of the LDH enzyme on the conversion of pyruvic acid to lactic acid was also investigated with variations in the ratio of crude enzyme to substrates being 10%, 15%, and 20% and variations in reaction temperature conditions were 27°C, 37°C, 47°C, and 57°C. The lactic acid obtained was then analyzed by means of High Performance Liquid Chromatography (HPLC). The results showed that the LDH enzyme had been successfully obtained from the extracts of corn seeds and roots. This is evidenced by the presence of a pyruvic acid curve from the results of HPLC analysis which shows that some of the pyruvic acid is converted to lactic acid and also from the results of the Bradford test which proves the presence of the LDH enzyme. However, in the results of the HPLC analysis curve, there are other products that are more dominant in quantity. It can be concluded that the extraction of LDH enzymes from corn kernels and roots reacted with pyruvic acid can be converted to lactic acid.